Sclerosing pneumocytoma in a 1-year-old girl presenting with massive hemoptysis: A case report. (February 2021) - Bara, Albaraa; Adham, Ibrahim; Daaboul, Obada; Aldimirawi, Fatima; Darwish, Bassam; Haffar, Lina
Abstract: Introduction and importance: Sclerosing pneumocytoma (SP) is a rare benign neoplasm of the lung with peak age incidence in middle aged-women. Here we report, for the first time in the literature, a case of a 1-year-old girl with SP. Case presentation: A 1-year-old girl was reported to emergency department for massive hemoptysis. After admission, the patient had a three-days episode of melena, with normal body temperature and generally stable condition. Clinical discussion: Fiberoptic bronchoscopy was normal. MSCT was done along with angiography and Three-Dimensional Reconstruction which revealed a well-circumscribed round mass with well-defined borders located near the vessels in the upper lobe of left lung. Anatomic lingula resection was performed. Hilar node was also resected. The histopathological examination confirmed the presence of SP. Fourteen months postoperatively, the patient was in a good health with no clinical or radiological evidence of recurrence. Conclusion: SP is a rare benign tumor which usually presents in middle aged-women asymptomatically or with nonspecific symptoms. We report this case to highlight that SP should be considered in cases of hemoptysis in young children. Highlights: Sclerosing Pneumocytoma could be asymptomatic or rarely present with hemoptysis. SP could be diagnosed in all ages including young children. Confirmed diagnosis of SP is made by histopathological study. Chest radiograph is non-specific in most SP cases.